2015
DOI: 10.5312/wjo.v6.i10.795
|View full text |Cite
|
Sign up to set email alerts
|

Anterior knee pain following primary total knee arthroplasty

Abstract: Despite improvements in technique and technology for total knee arthroplasty (TKA), anterior knee pain impacts patient outcomes and satisfaction. Addressing the prosthetic and surgical technique related causes of pain after TKA, specifically as it relates to anterior knee pain, can aid surgeons in addressing these issues with their patients. Design features of the femoral and patellar components which have been reported as pain generators include: Improper femoral as well as patellar component sizing or design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 63 publications
(130 reference statements)
0
31
0
Order By: Relevance
“…8,9,11 However, incorporating these design elements can theoretically result in potential problems. Although conformity between components increases the contact areas and stability, Shervin and colleagues 12 highlighted that increased conformity may lead to increased shear forces and potential adverse effects on fixation. Therefore, a balance between conformity and the "freedom to align itself" is sought.…”
Section: Femoral Componentmentioning
confidence: 99%
“…8,9,11 However, incorporating these design elements can theoretically result in potential problems. Although conformity between components increases the contact areas and stability, Shervin and colleagues 12 highlighted that increased conformity may lead to increased shear forces and potential adverse effects on fixation. Therefore, a balance between conformity and the "freedom to align itself" is sought.…”
Section: Femoral Componentmentioning
confidence: 99%
“…Abnormal patellofemoral biomechanics and patellar tracking play important roles in postoperative patellofemoral dissatisfaction, and the trochlear design is considered to be the main determinant [4,[6][7][8][9]. Compared to conventional designs with a neutral or symmetrical trochlear groove, the currently used femoral components with a lateral orientation or asymmetrical trochlear groove ("patellafriendly" design, with trochlear grooves that extend more proximally and orient more valgus compared to the native one) are believed to favor early patella capture and promote patellofemoral stability; however, the physiological patellofemoral kinematics, patellar tracking, and stability are not provided [6,[10][11][12][13]. Some biomechanical studies have shown that when influential factors such as component positioning, alignment, soft tissue balancing, and patellar resurfacing are controlled, the patellofemoral biomechanics are not fully restored to normal anatomy [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The patellofemoral anatomical morphology changed postoperatively, and the patellar motion followed an unphysiological trochlear groove. Compared with designs with a neutral or symmetrical trochlear groove (a symmetrical groove does not turn medially or laterally), the currently used femoral components with an asymmetrical trochlear groove ("patella-friendly" design, with trochlear grooves that extend more proximally and orient more valgus than the native one) are believed to favor early patella capture and promote patellofemoral stability; however, the physiological patellofemoral kinematics, patellar tracking, and stability have not been provided [5,7,8,12,13]. Some biomechanical studies have shown that when in uential factors such as component positioning, alignment, soft tissue balancing, and patellar resurfacing are controlled, the patellofemoral biomechanics is not fully restored to the normal anatomy [8,12].…”
Section: Introductionmentioning
confidence: 99%